Economic liberalization : an analysis of social mobility in Brazil - RODRIGUEZ PAEZ, Haroldo Emilio (2023)
Research on the impact of trade liberalization in Brazil and other countries has shown that these policies have had a significant impact on local labor markets, leading to higher unemployment and lower wages for less-educated workers. However, there is limited systematic evidence on the intergenerational effects of liberalization. Using Brazilian population censuses from 1980 to 2010 to estimate the social mobility variable, this study finds that the increase in economic liberalization during the 1991-2000 period reduced social mobility, but the negative effect doubled 20 years later. The negative impact on social mobility was greater for children with less educated parents. The study also found that formal employment and wage income decreased with liberalization, while informal employment increased. Robustness tests showed that the negative correlation between social mobility and economic openness was not affected, nor was the statistical significance of the estimates.